Low back pain in elite cross-country skiers. A retrospective epidemiological study - Eriksson, K.; Nemeth, G.; Eriksson, E. (Scandinavian Journal of Medicine & Science in Sports, 1996)
Low back pain is a common complaint among competitive cross-country skiers. Fifty-three top male and 34 female skiers in the age group 16-25 were interviewed with a questionnaire regarding anthropometric parameters, training variables, back pain and other injuries. The frequency of back pain was 64% in the whole group, men affected slightly more often than women. Back pain was defined as previous or present recurrent skiing correlated backache that more or less affected skiing ability. Diagonal skiing style was the most commonly back pain-inducing style, whereas no skier experienced back pain when "skating" only. The low back was the predominant location of pain. Anthropometric and training variables seemed to be of little value in predicting back pain.